2017
DOI: 10.3390/agronomy7010006
|View full text |Cite
|
Sign up to set email alerts
|

Biochar for Horticultural Rooting Media Improvement: Evaluation of Biochar from Gasification and Slow Pyrolysis

Abstract: Abstract:Peat is used as rooting medium in greenhouse horticulture. Biochar is a sustainable alternative for the use of peat, which will reduce peat derived carbon dioxide emissions. Biochar in potting soil mixtures allegedly increases water storage, nutrient supply, microbial life and disease suppression but this depends on feedstock and the production process. The aim of this paper is to find combinations of feedstock and production circumstances which will deliver biochars with value for the horticultural e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 47 publications
0
42
0
4
Order By: Relevance
“…To prevent high salinity, Blok et al . () suggest that feedstock salinity and alkalinity can be tested before biochar production, although a biochar's high EC can still be lowered by prior washing with water or by combining with a lower EC biochar. Furthermore, differences in biochar contributions to soil nutrient levels and plant physiological variables may also have affected maize biomass, as discussed below.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent high salinity, Blok et al . () suggest that feedstock salinity and alkalinity can be tested before biochar production, although a biochar's high EC can still be lowered by prior washing with water or by combining with a lower EC biochar. Furthermore, differences in biochar contributions to soil nutrient levels and plant physiological variables may also have affected maize biomass, as discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…High salinity can reduce plants' ability to uptake water and disrupt their nutritional balance (Corwin & Lesch, 2005); thus, the former biochars may have led to excessive soil salinity which, combined with high pH and other factors, impacted plant growth. To prevent high salinity, Blok et al (2017) suggest that feedstock salinity and alkalinity can be tested before biochar production, although a biochar's high EC can still be lowered by prior washing with water or by combining with a lower EC biochar. Furthermore, differences in biochar contributions to soil nutrient levels and plant physiological variables may also have affected maize biomass, as discussed below.…”
Section: Biochar Effects On Maize Biomassmentioning
confidence: 99%
“…Although research on the use of biochar as a peat replacement is not yet conclusive, the number of relevant publications is increasing very quickly. In the national research project Enerchar, conducted in cooperation with Wageningen University, some very successful pot trials have been performed that replaced up to 50% of peat (Blok et al 2017). The works of Steiner and Harttung, (2014), Vaughn et al (2015) and Kern et al (2017) support the notion that biochar can replace peat due to its high porosity, low density and high cation-exchange capacity.…”
Section: Description Of the Enerchar Co-production Systemmentioning
confidence: 99%
“…The works of Steiner and Harttung, (2014), Vaughn et al (2015) and Kern et al (2017) support the notion that biochar can replace peat due to its high porosity, low density and high cation-exchange capacity. The use of biochar produced from agro-and woody residual feedstocks as a substrate for soilless plant production can provide growers with a cost-effective and environmentally responsible alternative to the currently used peat substrates (Blok et al, 2017). In a very recent work, Margenot et al (2018) demonstrated that softwood biochar can be considered as a full replacement for peat in soil-free substrates at high rates (70% total substrate volume) for marigold production.…”
Section: Description Of the Enerchar Co-production Systemmentioning
confidence: 99%
“…Omol et al [3] in their recent research work involving conversion of municipal plastic wastes to fuel oil also reported the pyrolysis process as an effective approach to achieving their research objective. Findings from studies of Mary et al [4] and Block et al [5] have highlighted the benefits of biochar technologies, particularly concerning carbon sequestration via land application of biochar. According to [6] among all the available lignocellulose biomass, agricultural wastes such as corn stove, sugarcane bagasse, wheat straw and rice straw are produced in huge amounts globally [7].…”
Section: Introductionmentioning
confidence: 99%